Survei Minat Belajar Pendidikan Jasmani Dimasa New Normal Dalam Kemampuan Olahraga Atletik Siswa SMA N 1 Pamotan Kecamatan Pamotan Kabupaten Rembang - fredy eko setiawan; Andrey Wahyudi (JSH: Journal of Sport and Health, 2023)
Physical education as a component of education as a whole has been recognized by many groups. However, in practice teaching physical education has not been as effective as expected. Physical education learning tends to be traditional. The definition of physical education is often confused with other concepts. It equates physical education with any business or activity that leads to the development of the organs of the human body (body building), physical fitness, physical activities and skill development. In this study, a survey method was used, namely research that took samples from one population and used a questionnaire as the main data collection tool (Masri Singarimbun, 1989: 3). Based on the above understanding, the population in this study were all students of SMA Negeri 1 Pamotan 119 people consisting of 69 female students and 50 male students. Based on the results of the research and discussion above, it can be concluded that regarding the Interest in Learning Physical Education in the New Normal Period in Athletics Ability, there are 20 statements. From these results it can be obtained that the highest value is 82, the lowest value is 53, the average value is 66.45, the median or middle value is 66, the mode or value that appears most often is 71 and the standard deviation or deviation from the average is 6.630 .Â